mtHsp70 chaperone converts mitochondrial proteostasis stress into impaired protein import - Rupa Banerjee; Vanessa Trauschke; Nils Bertram; Ina Aretz; Christof Osman; Don C. Lamb; Dejana Mokranjac (Proceedings of the National Academy of Sciences, 2026)
Heat shock proteins 70 (Hsp70) represent a ubiquitous and conserved family of molecular chaperones involved in a variety of cellular processes. The conformational cycles of several Hsp70 chaperones, driven by ATP binding and hydrolysis, and regulated by cochaperones and substrate proteins, were analyzed in vitro in great detail. In contrast, little is known about the conformation Hsp70s adopt in their natural environments. In mitochondria, mtHsp70 is distributed between the TIM23 complex at the inner membrane, where it is involved in import of proteins from the cytosol, and a matrix-pool that is primarily involved in folding of proteins and prevention of their aggregation. Here, we used fluorescence microscopy to analyze the conformation of mtHsp70 at the single molecule level within physiologically active mitochondria. Our results revealed that the majority of mtHsp70 molecules are present in a substrate-bound state, suggesting that the mtHsp70 network functions at the limits of its capacity. To understand the biological significance of this finding, we modulated the levels of unfolded proteins in the matrix. Unfolded proteins reduced the association of mtHsp70 with the TIM23 complex and specifically impaired mtHsp70-dependent import of proteins. Our data show that unfolded proteins lead to a redistribution of mtHsp70 within mitochondria revealing how mitochondrial proteostasis stress is signaled to the cell—unfolded proteins remove mtHsp70 from the import sites, reducing the efficiency of protein import and initiating cellular programs to rescue or remove dysfunctional mitochondria. Thus, mtHsp70 acts as a mitochondrial quality control sensor that converts proteostasis stress into impaired protein import.